2002
DOI: 10.1016/s0038-1098(02)00475-1
|View full text |Cite
|
Sign up to set email alerts
|

Bulk-sensitive photoemission of Mn5Si3

Abstract: We have carried out a bulk-sensitive high-resolution photoemission experiment on Mn 5 Si 3 . The measurements are performed for both core level and valence band states. The Mn core level spectra are deconvoluted into two components corresponding to different crystallographic sites. The asymmetry of each component is of noticeable magnitude. In contrast, the Si 2p spectrum shows a simple Lorentzian shape with low asymmetry. The peaks of the valence band spectrum correspond well to the peak positions predicted b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…The substitution of Fe atoms to the 4d site affects electronic state of Mn atoms in this site and the chemical shift is significantly bigger. The valence band photoemission spectra of both compounds are very similar and agree qualitatively with the paper [6] as well as with our TBLMTO and published in [7] band structure calculations. On this basis we concluded that the enhancement of 3d Mn electronic states just below the sharp Fermi energy (see Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The substitution of Fe atoms to the 4d site affects electronic state of Mn atoms in this site and the chemical shift is significantly bigger. The valence band photoemission spectra of both compounds are very similar and agree qualitatively with the paper [6] as well as with our TBLMTO and published in [7] band structure calculations. On this basis we concluded that the enhancement of 3d Mn electronic states just below the sharp Fermi energy (see Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The Si atoms occupy also 6g site with the different values of the x parameter. The value of the x parameter are equal to 0.2358 (6) and 0.5992 (15) for Mn and Si, respectively. The atomic surroundings of Mn atoms at the different crystallographic positions are presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, is positioned at 46.9 eV, and cannot be described reliably by a fit procedure due to the presence of multiple overlapping peaks from the spin-orbit and multiplet splitting typical for 3d transition metals [20,[36][37][38]. The position of the main peak is commensurate with either Mn or Mn-silicides, or a mixture of both.…”
Section: Resultsmentioning
confidence: 99%
“…Surface CL shifts of the order of ∆E b ≈ 0.5 eV towards both higher and lower binding energies have been experimentally observed in different materials [1][2][3][4]. The magnitude and the sign of the shift depend on electronic and structural properties of the bulk and surface atoms, as well as on a surface structure.…”
Section: Introductionmentioning
confidence: 99%